2001
DOI: 10.1080/003655201750313351
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and Distensibility of the Rectum and Sigmoid Colon in Patients with Irritable Bowel Syndrome

Abstract: The visceral hypersensitivity in IBS seems to be related to alterations in the nervous system rather than biomechanical parameters such as the tension and strain of the gut wall. Treatment of pain in IBS should therefore be based on drugs with documented action on the nociceptive pathways in the central nervous system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 31 publications
3
37
0
1
Order By: Relevance
“…Rectal hypersensitivity is also a common finding in diarrhea-predominant irritable bowel syndrome (IBS), [7][8][9] and has been proposed as a biological marker of this generalized disorder of the gastrointestinal tract. 10,11 Such patients have symptoms of severe urgency and lose confidence in their ability to avert the call to stool.…”
mentioning
confidence: 99%
“…Rectal hypersensitivity is also a common finding in diarrhea-predominant irritable bowel syndrome (IBS), [7][8][9] and has been proposed as a biological marker of this generalized disorder of the gastrointestinal tract. 10,11 Such patients have symptoms of severe urgency and lose confidence in their ability to avert the call to stool.…”
mentioning
confidence: 99%
“…Nuestros resultados no avalan la presencia de alteraciones en la compliance rectosigmoidea en los pacientes con SII como causa de la hipersensibilidad, lo que ha sido demostrado por otros autores 16,[22][23][24] , siendo las características mecánicas de la pared colónica en estos pacientes comparables a los normales.…”
Section: Discussionunclassified
“…Some investigators found that the uncontrolled distension of a balloon in the sigmoid colon causes pain at lower volumes in patients with undefined IBS than in control subjects (18)(19)(20), but others could not confirm that conclusion (21). Measurements of pressures in balloons (rather than of balloon volumes) associated with such distensions of the sigmoid colon also yielded conflicting conclusions about hypersensitivity in IBS patients (22,23).…”
mentioning
confidence: 95%